Drawing the subsurface: an integrative design approach. (2017) - Hooimeijer, F.L.; Lafleur, F.; Trinh, T.T.
Abstract: The sub-surface, with its man-made and natural components, plays an important, if not crucial, role in the urban climate and global energy transition. On the one hand, the sub-surface is associated with a variety of challenges such as subsidence, pollution, damage to infrastructure and shortages of space for new urban systems. On the other hand, the sub-surface presents opportunities in terms of solutions for flooding, reduction in heat stress, and decentralized energy systems. Therefore, it is necessary to place sub-surface issues in their appropriate perspective, to enable a more resilient design that brings together ecosystem services, climate and urban systems, and which takes full account of the dynamics of the subsoil. To achieve this, the sub-surface must be an integral part of above ground planning and design. Organization of the sub-surface needs to be reflected visually in relation to - consideration of (surface) spatial morphology. The objective of this paper is to question the role of architectural representation of the subsurface. Discussion of architectural representation should include 'design thinking'. An important element of design thinking is the concepts that are used to guide the design process. For this reason, this research tests the role of visualization in relation to a case from the Dutch context and more specifically to subsidence. The approach is built on a systematic processing of contextual information of the site under development, using the System Exploration Environment, Subsurface and results in a Technical Profile. Using input from subsurface specialists to rethink the urban landscape results in realisation of synergies between subsurface elements and the (re)design of vital urban infrastructure.